Genre Analysis of Introductions of ELT Theses: Rhetorical Structures and Steps - Pandey, Gopal Prasad (Nepal Journal of Multidisciplinary Research, 2022)
The study of academic genres written by students has received considerable attention in ELT research in recent years. However, master's theses haven't garnered as much attention as Ph.D. dissertations have. This study examines the rhetorical structure of master's thesis introductions on ELT and applied linguistics at the Department of English education, Tribhuvan University, Kathmandu, Nepal. The analysis of the introductions is based on Swales’s (1990) CARS (Create-A-Research-Space) model. Based on the model, ten thesis introductions were analyzed in terms of the move structures and linguistic features that signal the use of the move. The study indicated that ELT thesis introductions employed all three moves proposed by Swales (1990) in its modified form (Bunton, 2002) at the macro level. Adopting the modified CARS model proposed by Bunton (2002), ELT thesis introductions written by Nepalese students employed six out of sixteen steps. The move structures of master’s thesis introductions were: move 1 (S1, S2 & S3), move 2 (S1 & S2), and move 3 (S1 & S7). This study will aid in the facilitation of academic writing instruction by providing the general framework of a good model of thesis introductory chapters.